2020
DOI: 10.1097/mrm.0000000000000201
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of FOX AmpC gene among Pseudomonas aeruginosa isolates in abattoir samples from south-eastern Nigeria

Abstract: In Nigeria, several investigations have been done about the prevalence of the AmpC enzyme in clinical isolates of Gram-negative bacteria; however, little information is available on the occurrence rate of this important enzyme in abattoir specimens that play a major role in the environmental pollution in Nigeria. This study aimed to evaluate the presence of FOX AmpC-producing Pseudomonas aeruginosa isolates from abattoir samples by both phenotypic method and polymerase chain reaction (PCR). In this study, 360 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The prevalence of GNB in slaughter houses and poultry farms is obvious due to the colonization of the gastrointestinal tract of animals with a variety of bacteria. However, since this high volume of bacteria may enter the human food chain and eventually lead to bacterial infections and the spread of antibiotic resistance, strict control policies should be implemented in the developing countries such as Nigeria to reduce the spread of MDR bacteria and increase the hygiene level of aforesaid environments [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The prevalence of GNB in slaughter houses and poultry farms is obvious due to the colonization of the gastrointestinal tract of animals with a variety of bacteria. However, since this high volume of bacteria may enter the human food chain and eventually lead to bacterial infections and the spread of antibiotic resistance, strict control policies should be implemented in the developing countries such as Nigeria to reduce the spread of MDR bacteria and increase the hygiene level of aforesaid environments [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The modified Kirby-Bauer disk diffusion method was used for AST as per the guideline of Clinical Laboratory Standard Institute (CLSI) using single antibiotic discs: imipenem (IPM), meropenem (MEM), ertapenem (ETP), cefoxitin (FOX), ceftazidime (CAZ), amikacin (AK), gentamicin (GM), cefotaxime (CTX), ceftriaxone (CRO), ciprofloxacin (CIP), ofloxacin (OFX), ampicillin (AMP), aztreonam (ATM) on Mueller-Hinton (MH) agar plate (Oxoid, UK) according to a previous methodology [ 15 , 35 ]. All test isolates were adjusted to 0.5 McFarland turbidity standard prior to culture and sensitivity study, and incubated at 37 °C for 18–24 h. The zone of inhibition was measured, recorded, and interpreted as susceptible (S), and resistant (R) using standard antibiotic breakpoints as stated by the CLSI [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Information was an important tool to modify irrational antimicrobial consumption in many countries [ 39 – 41 ]; however, in Latin America, these data are still lacking [ 26 ]. Although, there is no doubt that a high level of antimicrobial consumption is directly related to the level of bacterial resistance [ 42 ], antimicrobial usage patterns data are required to understand local resistance levels [ 43 , 44 ], including its use in animal production [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study by Zhu et al showed higher rate of these type of β-lactamases in their clinical setting [28]. It has been also investigated in non-clinical isolates of P. aeruginosa [5]. Low prevalence of this type of β-lactamases in P. aeruginosa in comparing to Enterobacteriaceae shows the lower potency of P. aeruginosa plasmids to harbor PBampC β-lactamases.…”
Section: Discussionmentioning
confidence: 99%